Strategi Komunikasi Pemasaran PT. Nojorono International Tobacco dalam Meningkatkan Brand Awareness - Refky Genta Saputra; Arfian Suryasuciramdhan; Agil Hari; Ehan Farhan; Muhammad Farhan Hidayatullah (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to analyze the sponsorship strategy implemented by PT Nojorono Tobacco Internasional in building brand awareness among generation Z through Community support events to Events organized by Authenticity. With the main target market of generation Z and Millennials, Authenticity utilizes music events as a platform to introduce products such as Clas mild Purple Duo and Clas mild Red Max that are relevant to their needs. This study uses a qualitative approach with a case study method and in-depth interviews with related parties at Authenticity and event organizers. The results of the study indicate that sponsorship through music events is effective in strengthening brand awareness, building emotional relationships, and increasing the engagement of the younger generation with the brand. The hypothesis proposed is that the integration of sponsorship with music events can improve the brand image of Clas Mild among generation Z. Based on these findings, it is recommended that Authenticity continue to optimize its sponsorship strategy in relevant events to strengthen brand engagement. This study emphasizes the importance of sponsorship strategies in building a strong and relevant brand image for young consumers.